Medication-Related Fall (MRF) screening and scoring tool: consensus Delphi validation. (1st April 2022) - Saeed, D; Miller, R; Darcy, C; Miller, K; Madden, K; McKee, H; Agnew, J; Crawford, P; Carter, G; Parsons, C
Abstract: Introduction: Falls are associated with negative health outcomes such as injury and mortality, as well as increased healthcare usage and costs. Risk factors for falls are multifactorial and include polypharmacy and the use of certain medications (1). Aim: To develop and validate a medication-related fall (MRF) screening and scoring tool. Methods: The MRF tool was developed from medication classes associated with falling in the Polypharmacy Guidance Realistic Prescribing 2018 (2), and additional medications identified and categorised by specialist and consultant pharmacists and physicians across a region of the United Kingdom. Medication classes were categorised as high-risk (three points), moderate-risk (two points) or low-risk (one point) in their 'potential to cause falls'. The overall medication-related fall risk for the patient was determined by summing the scores for all medications. The MRF was validated using Delphi consensus methodology, whereby three iterative rounds of online surveys were conducted using SurveyMonkey®. Delphi panel experts were defined as individuals with recognised expertise in geriatric medicine and pharmacotherapy in older people. Twenty-two experts determined their agreement with the falls risk associated with each medication on a 5-point Likert scale with accompanying written feedback. Only medications with at least 75% of respondents agreeing or strongly agreeing were retained in the next round. Following the first validation round, any proposed criteria that did not meet retention requirements were removed. The second and third rounds of the survey were created based on the panel comments from the previous round. Results: Consensus was reached for 19 medications/medication classes to be included in the final version of the MRF tool (table) and to reject eight medications/medication classes. Consensus was not reached regarding eight medications and they were not included in the final version of the tool. Conclusion: The MRF tool is simple and feasible to use in healthcare settings to evaluate and optimise medications as a standalone screening instrument or as part of a multidisciplinary intervention to reduce fall risk and negative fall-related outcomes. The score from the MRF tool has potential for use as a clinical parameter to evaluate prescribing appropriateness. References: (1) Public Health England (2020) Falls: applying All Our Health. Available at https://www.gov.uk/government/publications/falls-applying-all-our-health/falls-applying-all-our-health Guidance Falls: applying All Our Health. (Accessed: 4th April 2020) (2) Scottish Government Polypharmacy Model of Care Group (2018). Polypharmacy Guidance, Realistic Prescribing. 3rd Edition.